Edge detection based on fractional order differentiation and its application to railway track images. Issue 1 (21st October 2015) - Telke, Christian; Beitelschmidt, Michael
Abstract Edge detection is one of the most fundamental necessities in image processing. Usally, edge detection algorithms are based on integer order differentiation operators. In many applications it is essential to perform a robust edge detection also to noisy input image data with low SNR as well. Thereby, integer based differentiation operators are often not leading to sufficient detection results. For this purpose an edge detector based on fractional order differentiation is introduced, which can significantly improve the detection performance to noisy images. Furthermore, a real application scenario of fractional order based edge detection is given within a modular railway track measurement system. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)